2018
DOI: 10.1021/acsami.8b06229
|View full text |Cite
|
Sign up to set email alerts
|

Stable Covalent Organic Frameworks as Efficient Adsorbents for High and Selective Removal of an Aryl-Organophosphorus Flame Retardant from Water

Abstract: A critical challenge in environmental remediation is the design of adsorbents with proper pore size for the removal of organic pollutants. Three covalent organic frameworks (COFs) with different pore sizes were successfully prepared by a room-temperature solution-suspension method and used to remove a typical aryl-organophosphorus flame retardant [triphenyl phosphate (TPhP)] from aqueous solution. The prepared COFs showed strong acid resistance and thermal stability. The 1,3,5-triformylphloroglucinol (TFP) rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(61 citation statements)
references
References 42 publications
1
60
0
Order By: Relevance
“…Meanwhile, Wang et al . reported that the synthesis of COPs could be achieved by a simple solution‐suspension method under ambient conditions at room‐temperature . The mentioned above strongly promotes us to believe that exploring novel sophisticated and multi‐component COPs through a simple, facile and cost‐effective approach is feasible in theory to settle environmental issues.…”
Section: Methodssupporting
confidence: 71%
“…Meanwhile, Wang et al . reported that the synthesis of COPs could be achieved by a simple solution‐suspension method under ambient conditions at room‐temperature . The mentioned above strongly promotes us to believe that exploring novel sophisticated and multi‐component COPs through a simple, facile and cost‐effective approach is feasible in theory to settle environmental issues.…”
Section: Methodssupporting
confidence: 71%
“…COFs are usually obtained as low-density powders featuring polydisperse particles with sizes in the micrometer range. Althoughs uch powder can be directly applied for adsorption of contaminants in water using different modalities, such as direct dispersion in sample matrices [35,37,44,47,48,50,51,53,54] or packing into columns, [39,125] using the bulk material could lead to materiall osses, high column backpressure, and difficulties in its isolation from the sample matrix. These are serious limitations, which can hinder the use of COFs in environmental applications.…”
Section: Concept Cof Formulationsmentioning
confidence: 99%
“…The frameworks explored for this applicationh ave typicallyf eatured either tetragonal or hexagonal pores (Scheme 1). Promising results have been obtained for the captureo f, for example, organic dyes, [31][32][33][34][35] perfluoroalkyl substances, [36] aryl-organophosphorous flame retardants, [37] pesticides, [38][39][40] phenol endocrine disruptors, [41,42] lactic acid, [43] iodine, [44,45] mercury, [46][47][48][49] radionuclides, [50] lanthanides, [51] and oil spills. [52] We found COFs to efficiently adsorb biotoxins from seawater [53] andp harmaceuticalc ontaminants from water, [54] expanding their use to these classes of hazardouscompounds.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with their materials similar to metal organic frameworks (MOF), robust covalent bonds on COF enable it to overcome the problems of water and moisture instability [16,17]. The fascinating features such as low density, high and regular porosity, tunable pore size [18,19], render them promising candidates in diverse applications in catalysis, gas storage, adsorption, optoelectricity and chemical sensors [20][21][22][23][24]. Recently, some research has reported that COF can heterogeneously nucleate and grow on the surface of different matrices to construct core-shell structure composite materials (graphene, carbon nanotubes, Fe 3 O 4 and alumina, etc.)…”
Section: Introductionmentioning
confidence: 99%